Malignant Peripheral Nerve Sheath Tumor of Lacrimal Nerve: A Case Report. (February 2015) - Rajabi, Mohammad Taher; Riazi, Hamid; Hosseini, Seyedeh Simindokht; Rajabi, Mohammad Bagher; Mazloumi, Mehdi; Gharehbaghi, Golnaz; Amoli, Fahimeh Asadi
Abstract Background: Orbital and periorbital presentation is rare for malignant peripheral nerve sheath tumors. These tumors are poorly defined spindle cell neoplasms of peripheral nerves and have not been reported to develop in the lacrimal gland to date. Aim: To report a rare presentation of malignant peripheral nerve sheath tumor in the orbital cavity. Case report: A 65-year-old man was admitted with the chief complaint of prominent right eye. His symptoms began 16 months prior to his admission. He had obvious limited ocular motion in upgaze and lateral gaze directions, as well as diplopia in all directions. He underwent imaging studies, and an iso-dense mass lesion in the lacrimal gland was revealed in orbital CT scan. In the MRI, there was a well-defined iso-intense mass lesion in T1-weighted images that was hyperintense in T2-weighted images and was enhanced with Gadolinium. Excisional biopsy revealed epithelioid and spindle cells with hyperchromatic rather than pleomorphic nuclei. Immunohistochemistry confirmed the presence of positive markers consistent with malignant peripheral nerve sheath tumor. Conclusion: Malignant peripheral nerve sheath tumor should be considered in the differential diagnosis of lacrimal gland tumors. Imaging studies may be helpful but tissue biopsy should be performed for accurate diagnosis. Complete excision of the mass lesion and adjunctive chemotherapy and radiotherapy should be considered in these cases.